Factores que determinan el emprendimiento femenino en las microempresarias de la ciudad de Requena, 2023 - Uribe Ochavano, Diana Cristina (2023)
The general objective of the report was to identify the factors that determine female entrepreneurship in microentrepreneurs in the city of Requena, 2023, where it was decided to carry out an applied study of an explanatory level with a non-experimental design, taking as a sample all of the the population, that is, the 70 microentrepreneurs who were surveyed through a questionnaire for the collection of information. According to the results obtained, there is a high prevalence of women with the potential to undertake between 40 and 50 years of age, who manage to maintain an independent source of income, as well as a preponderance of women from rural areas who show outstanding conditions for entrepreneurship. In addition, a significant influence (0.000) was determined between personality traits and female entrepreneurship; the capacity in female entrepreneurship; but the environment does not have a significant influence (0.090) on female entrepreneurship, since they maintain a very low relationship.